THE TRADITIONAL HEAD HUNTING PRACTICES OF THE LUHUPPAS. - Dr Jacob Luiram * and Soyaphy Khangrah ** (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
The Luhuppa (Tangkhul Naga tribe) is one of the oldest and largest tribe of Manipur. The forefathers of the Luhuppas (Tangkhuls) of Manipur were head hunters. Head hunting or chopping of enemies’ head was an important aspect of the Luhuppas and when we talk about the history of the Luhuppa (Tangkhul) community, the traditional practice of head hunting is inevitable. Head hunting meant killing enemies by chopping off the enemies head and carried home the head as a sign of victory. The Luhuppas are warrior tribe existed in isolation and their relationship with others was neither fraternal nor neighbourly. They are self-sufficient community and remained cut off from the rest of the world for many centuries. Head hunting were practiced based on their traditional religious faith, security purpose and social significance. Training of head hunting was given for village defence and self-defence. Brave head hunters were given respect, fame and titles. The Luhuppa tribe has strict adherence to traditional customary law of war. There was no random killing of people just for head. The practice of head hunting had economic values and political consideration. Head hunting practice gradually came to an end by the beginning of the 20th century with the coming of Christianity.